CFD analysis of two types of welded plate heat exchangers. (1st February 2017) - Luan, H. B.; Kuang, J. P.; Cao, Z.; Wu, Z.; Tao, W. Q.; Sundén, B.
ABSTRACT: A numerical and experimental study has been carried out on the heat transfer and fluid flow in two types of welded plate heat exchangers (PHEs). A new approach providing a proper clearance between two adjacent corrugated plates is proposed to improve the mesh quality around the contact points. The clearance value and the influence on the mesh quality and computational results are carefully studied. The results show that a relative clearance of 0.02 is proper. The computational fluid dynamics (CFD) results agree with the experimental results with a deviation of 15%. The proposed approach is proved effective and practical because it can increase the grid quality without losing the accuracy of the results. This paper shows that CFD is a reliable tool for studying the effects of various geometrical configurations on the optimum design of a PHE.